Odpowiedzi

2009-12-03T19:26:13+01:00
E) 2(3x-2y+3z)-5(x-y-z) = 6x-4y+6z-5x+5y+5z = x+y+11z
f) 4x(x-y-z)-2x(4x-y+z) = 4x²-4xy-4xz-8x²+2xy-2xz = -4x²-2xy-6xz
g) -3x²(x-⅔y)+5x(x²-7xy) = -3x³+2x²y+5x³-35x²y = 2x³-33x²y
Mam w 100% dobrze bo mam te samą książkę i odpowiedzi się zgadzają.
27 4 27
2009-12-03T19:27:50+01:00
E)2(3x-2y+3z)-5(x-y-z)
6x-4y+6z-5x+5y+5z
x+y+11z
f)4x(x-y-z)-2x(4x-y+z)
4x²-4xy-4xz-8x²+2xy-2xz
-4x²-2xy-6xz
g)-3x²(x-⅔y)+5x(x²-7xy)
-3x³+2x²y+5x³-35x²y
2x³-33x²y
16 3 16
Mi jest potrzebne a,b,c,d może macie ?